Optimasi kecepatan putar pengadukan dan waktu pengadukan terhadap kualitas fisika biodiesel dari minyak kelapa - Riny Andwika Simatupang (PILLAR OF PHYSICS, 2016)
Nowadays, the quantity of fuel in the nature almost depleted. This condition make us to find another alternate energy source as a solution of fuel limitation.Using the organic material like cocoa plant as a renewable fuel that is biodiesel, to replace the diesel. This research goal is to know the optimum point of velocity of stirrer and stirring duration so it could produce fine quality of biodiesel as alternative energy source. In this research, the free variable that applied to the mixer as stir velocity is 1050 rpm, 1100 rpm, 1200 rpm and stir duration is been done in 5, 10, 15, 20 and 25 minutes. For controlled variable like process temperature is 50◦C, with sedimentation time is 24 hours and using NaOH as catalyst Biodiesel that been produce from transesterification from coco oil, having viscosity point at 4.408 cSt, density at 872.995 kg/m3 and flashpoint > 100◦C. The condition obtain from stirrer that using speed 1100 rpm on 5 minutes as the stirring time